RELEVANSI PENEGAKAN HUKUM DITINJAU MENURUT UNDANG-UNDANG PEMBERANTASAN TINDAK PIDANA KORUPSI Analisis Putusan Nomor : 05 /Pid.Sus/TPK/2015/PN.Sby - Abdul Hakim; Mohammad Bangsu (JURNAL LEGISIA, 2022)
The crime of corruption always gets more attention than other criminal acts because the impact it causes covers various aspects of life, especially in the Indonesian state considering that corruption itself is a crime that is mushrooming and has become a tradition that is increasing every year, it is evident from the various cases that have appeared in the mass media, both print media and electronic media corruption is a social phenomenon which is the reality of human behavior in the interaction of society and the state. The approach to this problem is carried out with a normative juridical approach, with regard to the question of whether the influence of legal rules is in accordance with the wishes of the community